Evidence of Augmented Intrarenal Angiotensinogen Associated With Glomerular Swelling in Gestational Hypertension and Preeclampsia: Clinical Implications. Issue 13 (2nd July 2019) - Mistry, Hiten D.; Kurlak, Lesia O.; Gardner, David S.; Torffvit, Ole; Hansen, Alastair; Broughton Pipkin, Fiona; Strevens, Helena
Abstract : Background: AGT (angiotensinogen) synthesis occurs in renal proximal tubular epithelial cells, independent from systemic AGT, as a component of the intrarenal renin–angiotensin system. We investigated urinary AGT, as a biomarker for renin–angiotensin system activation, and electrolyte concentrations, in relation to glomerular volume, as a proxy for glomerular endotheliosis in renal biopsy tissue from pregnant normotensive control and hypertensive women. Methods and Results: Urine samples were collected from normotensive control (n=10), gestational hypertensive (n=6), and pre‐eclamptic (n=16) women at the time a renal biopsy was obtained. Samples were collected from Lund University Hospital between November 1999 and June 2001. Urinary AGT, potassium, and sodium were measured, normalized to urinary creatinine. Mean glomerular volume was estimated from biopsy sections. AGT protein expression and localization were assessed in renal biopsies by immunohistochemistry. Urinary AGT concentrations were higher in hypertensive pregnancies (median, gestational hypertension: 11.3 ng/mmol [interquartile range: 2.8–13.6]; preeclampsia: 8.4 ng/mmol [interquartile range: 4.2–29.1]; normotensive control: 0.6 ng/mmol [interquartile range: 0.4–0.8]; P <0.0001) and showed a positive relationship with estimated mean glomerular volume. Urinary potassium strongly correlated with urinary AGT ( P <0.0001). Although numbers were small, AGT protein was found in both glomeruli and proximal tubules in normotensive control but was present only in proximal tubules in women with hypertensive pregnancy. Conclusions: This study shows that pregnant women with gestational hypertension or preeclampsia have increased urinary AGT and potassium excretion associated with signs of glomerular swelling. Our data suggest that the kidneys of women with hypertensive pregnancies and endotheliosis have inappropriate intrarenal renin–angiotensin system activation, which may contribute toward the pathogenesis of hypertension and renal injury.